PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PENGEMASAN DAN PEMASARAN BERBASIS DIGITAL PADA KELOMPOK UMKM OPAK DESA PAJATEN - Hardi, Mukhyar; Hidayat, Dayat; Meilya, Ika Rizqi (IKIP Siliwangi, 2025)
Community empowerment is basically a planned social change strategy to overcome dilemmas or meet community needs. The formulation of the research problem is how the process of implementing women's empowerment through digital-based Opak UMKM packaging and marketing training in Pajaten Village. The method used in this study is qualitative descriptive research. The research subjects were divided into four respondents, including the first respondent, namely the group leader (R1), the second respondent, namely the tutor (R2), two respondents as learners from the women's group (R3 and R4) and the fifth respondent (R5) the organizer. The data analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that packaging and marketing training was carried out directly by combining theory and practice, with a focus on important skills such as packaging design, digital marketing, product photography, SEO, and the use of social media. This training has a significant impact on increasing the knowledge, skills, and economic independence of participants. However, in its implementation, there are obstacles, namely access to technological devices and the quality of facilities are the main challenges that must be overcome to ensure the learning process runs optimally.